SDG’s DAN PERANAN PERGURUAN TINGGI MENCIPTAKAN SOCIAL ENTREPRENEUR PADA MAHASISWA - Sari Anita Dian; Susanti, Savira; Mutaallimah, Akfina; Chanifatur Rohmah (BBM (Buletin Bisnis & Manajemen), 2018)
The role of the young generation, especially students in succeeding SustainableDevelopment Goals (SDG's) is very important. According to statistical data, the number ofstudents in Indonesia is about 30% of the total number of productive ages. In the achievementof success at a young age, students' self‐ability should be sharpened and developed, one of themwith entrepreneurship. Entrepreneurship using the base of social entrepreneur be a goodalternative in exploiting the potential in Rembang regency. Students as a generation of change,is expected to be able to entrepreneurship with the base of social entrepreneurs who not onlypursue profit but also beneficial to the surrounding environment that is prioritizing the welfareof the community. With the growing number of students who are entrepreneurial entrepreneursor students who help the community for the purpose of social thinking about the environmentalconditions for the long term in order to create sustainable economic development. This conceptwill have a positive impact towards Sustainable Development Goals (SDG's) 2030. To realize thesocial entrepreneur among the students certainly can not be separated from the role ofuniversities. Study literature review using literature studies obtained from journals, books, andarticles are accurate. The writing method uses descriptive qualitative analysis. The results of thisstudy is the role of universities and the steps and efforts that can be done by students to becomesocial entrepreneurs by exploiting the potential of existing potential in the district of Rembang.Keywords: University Student, Entrepreneur, Social Entrepreneur